G235(P) Isolated fetal hydronephrosis: sonographic predictors of adverse postnatal outcome. (May 2019) - Wilkins, J; Lambert, H; Robson, S
Abstract : Background: Hydronephrosis (HN) is identified in 1% of fetuses and may be isolated or associated with other abnormal ultrasound features (e.g. bladder or ureteric dilation.) Isolated HN can result from pelvi-ureteric junction obstruction (PUJO), which is associated with increased risk of urinary tract infection and surgery or can be a benign variant. Aims: To determine antenatal ultrasound predictors of (a) significant PUJO (b) surgery in infants with persistent postnatal HN. This should allow more accurate prenatal counselling and help guide postnatal management. Methods: Fetuses with HN (maximum third trimester renal pelvis antero-posterior diameter [RPAPD] measurement ≥10 mm) referred to regional perinatal renal service between 2010–2016 were prospectively identified. Data were collected on prenatal ultrasound findings and postnatal outcomes. Independent antenatal predictors were determined using binary logistic regression. The optimal RPAPD to differentiate between cases with and without an adverse postnatal outcome was determined by ROC curve analysis. Significant PUJO was defined as a split function of <40% on a MAG 3 scan. Parenchymal abnormalities were defined as cystic or echogenic appearance of the renal cortex on antenatal ultrasound. Results: 192 fetuses (222 renal units) were identified with isolated HN. The optimal RPAPD cut-off was 15 mm for both outcomes; the sensitivity and specificity of this measurement for significant PUJO was 83% and 78% respectively and for surgical intervention 86% and 69% respectively. Predictors of renal units with significant PUJO were calyceal dilation, parenchymal abnormality and RPAPD ≥15 mm with odds ratios (OR, 95% CI) of 6.0 (1.6–23.2), 9.00 (2.6–31.5) and 15.8 (3.3–75.6) respectively. The same predictors were found for renal units undergoing surgical intervention; with respective ORs of 5.6 (95% CI 2.0–15.7), 8.0 (95% CI 2.5–25.2) and 10.3 (95% CI 3.3–31.6). Conclusion: Predictors of adverse outcomes were maximum third trimester RPAPD, calyceal dilation and parenchymal abnormalities. The optimum RPAPD cut-off point to determine those at risk of poor outcomes was 15 mm, but the specificity was poor thus key adverse outcomes cannot be reliably predicted by prenatal ultrasound.